Improving Students’ Economic Learning Outcomes through Problem-Based Learning Methods - Marliah, Esy; Kumar, Atul (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to evaluate the effectiveness of the problem-based learning method (PBL) in improving student learning outcomes in economics subjects at SMA Negeri 15 Palembang. The research method used was a quasi-experimental with a non-equivalent control group design, involving two classes of XI IPS selected as the experimental and control groups. The experimental group received economics learning with the PBL method, while the control group used conventional learning methods. Data were collected through learning outcome tests (pre-test and post-test) and analyzed using paired sample t-tests and independent sample t-tests to determine significant differences in learning outcomes between the two groups. The results showed that there was a significant increase in the learning outcomes of the experimental group compared to the control group. The average post-test score in the experimental group was higher than in the control group, indicating that the PBL method is effective in improving students’ understanding and critical thinking skills in economics material. In addition, observations during learning showed that the PBL method increased students’ active involvement in group discussions and problem-solving processes. This study concludes that the PBL method is an effective approach to improve students’ economic learning outcomes and can be used as an alternative learning method in the school curriculum. Recommendations are given for teachers to receive training to implement PBL optimally, as well as support from the school in providing adequate resources. The implication of this study is that PBL not only improves academic learning outcomes but also students’ collaborative and independent skills, which are important to face the challenges of 21st-century education.